1996
DOI: 10.1086/310044
|View full text |Cite
|
Sign up to set email alerts
|

A Counterrotating Bulge in the Sb Galaxy NGC 7331

Abstract: We have found that the bulge of the large, nearby Sb galaxy NGC 7331 rotates retrograde to its disk. Analysis of spectra in the region of the near-IR Ca II triplet along the major axis shows that, in the radial range between 5 ′′ and ∼20 ′′ , the line of sight velocity distribution of the absorption lines is has two distinct peaks, and can be decomposed into a fast-rotating component with v/σ > 3, and a slower rotating, retrograde component with v/σ ∼ 1 -1.5. The radial surface brightness profile of the counte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
73
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 28 publications
11
73
0
Order By: Relevance
“…Often galaxy disks show a number of kinematically distinct components like counter-rotating bulges (Prada et al 1996), counter-rotating disk stars (Vergani et al 2007;Coccato et al 2011), and SF regions kinematically decoupled from the rest of the galaxy Koleva et al 2014). These features are Combes et al (2013).…”
Section: Kinematical Distortionsmentioning
confidence: 99%
“…Often galaxy disks show a number of kinematically distinct components like counter-rotating bulges (Prada et al 1996), counter-rotating disk stars (Vergani et al 2007;Coccato et al 2011), and SF regions kinematically decoupled from the rest of the galaxy Koleva et al 2014). These features are Combes et al (2013).…”
Section: Kinematical Distortionsmentioning
confidence: 99%
“…As dynamically cold streams of stars fall back into the remnants, they wrap around the center and form sharp-edged features at their turnaround points (Hernquist & Spergel 1992;Hibbard & Mihos 1995). The high percentage (∼70%) of field ellipticals featuring such fine structure (Schweizer & Seitzer 1992) and the considerable amounts of material indicated by integrated photometry (Prieur 1990) suggest that most of the observed fine structure cannot be due to mere dwarf galaxies falling in. Instead, such structure is much more likely the signature of past major mergers that formed most, or even all, ellipticals.…”
Section: Ellipticals From Wrecked Disksmentioning
confidence: 99%
“…Kuijken et al 1996), there are only two known galaxies with large counterrotating stellar disks; NGC 4550 (Rubin et al 1992) and NGC 7217 (Merrifield & Kuijken 1994). There are a few cases which do contain counterrotating stellar disk components, but where the secondary component is much less extended than the primary one and is confined to the central region: NGC 3593 (Bertola et al 1996), NGC 4138 (Jore et al 1996) and NGC 7331 (Prada et al 1996). On the other hand Bertola et al (1992) and Kuijken et al (1996) report that ∼20-25% of all gas disks found in S0 galaxies counterrotate with respect to the stars.…”
Section: Introductionmentioning
confidence: 99%